Interactive Multimedia Applications "Know Your Computer Components" Using the swish Max - Seno Dimas Bintoro; Yulina Yulina, Skom, MMSi (Jurnal Sistem Informasi, 2003)
Nowadays with the advancement of science and technology and advances in the computer world in particular, many people utilization of computer technology in all areas of life, as in the field of medical science, education and others. Computer is not just another luxury item for the middle class and above, but has become an important need in life. An ordinary computer users sometimes can only use the computer in general, they did not know more about the components in a computer. Usually to get to know more about their components in a computer search of existing books. Sometimes in a book less attractive appearance to his readers so that readers are less interested in reading. Therefore, in order to increase the interest our readers, we need a renewal, ie make a program familiar with the interactive multimedia application components of a computer, so that readers are more interested to know the ins and outs of a computer.